How do European RIs Contribute to Tackling Grand Societal challenges? Views from the Humanities - Žic Fuchs, Milena (Array, 2012)
The presentation covered the topic of the necessity of developing Research Infrastructures in the Humanities and Social Sciences, especially in view of inter/multi/transdisciplinarity research in the Grand Challenges. Databases of these kinds are essential for establishing networks of knowledge bringing together research from different domains and taking into account differences in cultural backgrounds in knowledge.